The modern construction of nursing - Domingo Palacios Ceña (Universidad de Alicante, 2012)
Modern times together with positivism marked and determined the way to build and understand the world between XVII and XIX century, being the main instruments technology, reason and science, turning efficiency, aim and pragmatism into essential and necessary elements within our way of living to perceive our environment and relationships. Nursing as a discipline and health care as object of study were not considered far from this influence, in fact many nursing elements and health care elements are saturated with part of that modern positivism thought. The present study describes modern and positivism characteristics as well as how there exist elements within nursing built from a modern perspective. Among others, the way of planning nursing activities in hospitals, lost of the individual's complexity, modern ethics, paradigms and research in nursing, health care as a study object and the meaning of technology in nursing.